A massive 13.5 cm sclerosing pneumocytoma in a 61-year-old female - Sampson K. Boham; Kenneth A. Kesler; Merideth E. Geib; Xiaoyan Wang (Elsevier, 2021)
Sclerosing pneumocytoma (previously called pulmonary sclerosing hemangioma) is a very rare benign pulmonary neoplasm. Diagnosis of this tumor can be problematic especially on the small biopsy specimens. Here, we report a massive 13.5 cm sclerosing pneumocytoma in a 61-year-old female who presented with progressive shortness of breath and underwent lobectomy procedure. Radiological findings, gross and histological features, immunohistochemical staining profile as well as differential diagnoses are discussed in detail. The purpose of this case study is to increase awareness of this entity among physicians and to further aid in proper clinical management.